A strain-based approach to study interaction between non-coplanar through-thickness edge notches. (November 2018) - Samadian, Kaveh; Hertelé, Stijn; De Waele, Wim
Structural integrity assessment procedures to assess the effect of interaction between multiple adjacent flaws normally consist of two stages. First, alignment rules categorize non-coplanar flaws as aligned or non-aligned. Second, combination rules classify aligned flaws as interacting or non-interacting. Although these criteria are applied to different failure modes like brittle fracture, elastic–plastic fracture and plastic collapse, most of them were developed based on linear elastic fracture mechanics for the sake of simplicity. However, there are very limited references available for the technical background of these criteria. This lack of justifying backgrounds becomes more critical when applying these procedures to any other failure modes other than brittle fracture. This article studies the interaction between non-coplanar edge notches in scenarios of large deformation. Hereto, strain patterns are studied through full-field deformation measurements utilizing both experimental and numerical tools. Digital image correlation is used to measure strain during experiments and to verify the finite element analyses. The results show that in addition to the crack driving force, which represents a local response of notches, the global strain distribution within the specimen in terms of strain patterns can be used to probe the interaction between non-coplanar flaws. The authors suggest a novel criterion based on the trajectory of maximum equivalent strain to distinguish between aligned and non-aligned flaws. This study is based on double-edge notched tension specimens and gives a fundamental insight into flaw interaction in failure modes other than brittle fracture.